筋萎縮性側索硬化症及び関連する疾患の治療 (2023)
本発明は、ＡＬＳの少なくとも１つの症状を治療するための方法及び組成物、ＡＬＳ疾患の進行を遅らせる方法、又は対象においてＡＬＳによって影響を受けた１つ以上の身体の機能低下を軽減する方法に関する。この方法は、胆汁酸又はその薬学的に許容される塩及びフェニル酪酸化合物を対象に投与することを含むことができる。 Provided herein are methods and compositions for treating at least one symptom of ALS, slowing ALS disease progression, or reducing the deterioration of one or more bodily functions affected by ALS in a subject. The methods can include administering to the subject a bile acid or a pharmaceutically acceptable salt thereof and a phenylbutyrate compound.